2010
DOI: 10.1037/a0019010
|View full text |Cite
|
Sign up to set email alerts
|

Emotion regulation and vulnerability to depression: Spontaneous versus instructed use of emotion suppression and reappraisal.

Abstract: Emotion dysregulation has long been thought to be a vulnerability factor for mood disorders. However, there have been few empirical tests of this idea. In this study, we tested the hypothesis that depression vulnerability is related to difficulties with emotion regulation by comparing recovered-depressed and never-depressed participants (N = 73). In the first phase, participants completed questionnaires assessing their typical use of emotion regulation strategies. In the second phase, sad mood was induced usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
345
2
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 495 publications
(384 citation statements)
references
References 52 publications
(73 reference statements)
31
345
2
6
Order By: Relevance
“…Affective disorder research provides some support for the notion that individual differences in psychopathology may have little effect on positive reappraisal implementation in the lab. Behavioral evidence indicates, for example, that when anxious and depressed people are asked to implement strategies that involve different reappraisal operations, they can be successful (Campbell-Sills, Barlow, Brown, & Hofmann, 2006;Ehring, Tuschen-Caffier, Schnülle, Fischer, & Gross, 2010; also see, Kross & Ayduk, 2009;Kross, Gard, Deldin, Clifton, & Ayduk, 2012). Such patients also respond well to therapies whose primary technique is cognitive reappraisal (Clark & Beck, 2010).…”
Section: From the Lab To Everyday Life: Trait Reappraisal And Worrymentioning
confidence: 99%
“…Affective disorder research provides some support for the notion that individual differences in psychopathology may have little effect on positive reappraisal implementation in the lab. Behavioral evidence indicates, for example, that when anxious and depressed people are asked to implement strategies that involve different reappraisal operations, they can be successful (Campbell-Sills, Barlow, Brown, & Hofmann, 2006;Ehring, Tuschen-Caffier, Schnülle, Fischer, & Gross, 2010; also see, Kross & Ayduk, 2009;Kross, Gard, Deldin, Clifton, & Ayduk, 2012). Such patients also respond well to therapies whose primary technique is cognitive reappraisal (Clark & Beck, 2010).…”
Section: From the Lab To Everyday Life: Trait Reappraisal And Worrymentioning
confidence: 99%
“…In addition, changes in mood itself following mood provocation (i.e., mood reactivity [MR]) also appear to be related to relapse in depression (Ehring, Fischer, Schnülle, Bösterling, & TuschenCaffier, 2008;Ehring, Tuschen-Caffier, Schnülle, Fischer, & Gross, 2010;Lethbridge & Allen, 2008). This implies that the inability to effectively regulate affect during emotional or stressful events could signal the return of depressive symptomatology.…”
mentioning
confidence: 99%
“…As for adaptive strategies, the converse would be expected (i.e., reliable negative associations with psychopathology) but this finding is less consistent. In some studies, no relation between adaptive strategies and psychopathology is reported (Domínguez-Sánchez et al, 2013;Ehring, Tuschen-Caffier, Schnülle, Fischer, & Gross, 2010;Green et al, 2011). In a meta-analytic review, using normative and clinical samples, adaptive strategies were found to be associated with decreased psychopathology, but the associations had small to medium effect sizes (Aldao, Nolen-Hoeksema, & Schweizer, 2010).…”
mentioning
confidence: 99%